USING ROSETTA PROGRAM IN DETERMINING HYDRAULIC PROPERTIES OF THREE DIFFERENT MOUNTAINOUS TEXTURED SOILS UNDER SEMIARID CONDITIONS OF DUHOK IRAQI – KURDISTAN - KHALAF, AKRAM ABBAS (Journal of Duhok University, 2022)
This study was carried out in three mountainous different soil textures and two depths. Field measurements of soil texture and bulk density, and laboratory measurements of soil water retention at field capacity (–33 kPa) and permanent wilting point (–1500 kPa), were taken to implement Rosetta. Calculated values of van Genuchten parameters were then compared to measured values. Results showed that Rosetta could be used to obtain values of van Genuchten parameters for a field with different soil textures. The determination coefficient (R2) of It showsthat 50% of determination coefficients(R2) gave more than 0.99 and 30% gave more than 0.98 and the others gave between (0.91-0.97) at applying the (PTFs) at two depths for the studied soils. The Root Mean Square Difference (RMSD) indicated that the lowest values of RMSE were exhibit by all soils (Zawita, Swaratoka and Koradare) and two depths D1 and D2 except D1 of Swaratoka Clay loam soil and at different textures.NSE elevation indicator revealed that the maximum values more than (0.99) were found in Zawita loamy soil and at depth two, D2 whereas the minimum values were noticed in Koradare Silty Loam and at depth two,D2. We conclude that Rosetta is a tool that can be used to calculate van Genuchten parameters the absence of measured values, for the studied soils(Zawita, Swaratoka and Koradare) Rosetta Levels yielded the best results as following: Level 5 gave highest (R2) at applying in (Zawita,D1-Swaratuka and KoradareD2), lowest RMSE and maximum in (Koradare,D2) using the measured input data and thus calculated values ofvan Genuchten parameters can be used as input in simulation models